2004
DOI: 10.1002/app.21097
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of silica‐filled poly(2‐hydroxymethyl methacrylate) nanocomposites cured by photoirradiation during the sol–gel process

Abstract: ABSTRACT:The sol-gel process was used to prepare a photosensitive inorganic-organic composite, silica/poly(2-hydroxymethyl methacrylate). Its nanoscale morphology was observed with field emission scanning electron microscopy at high magnifications (e.g., 160,000ϫ). The size of the particles in the nanocomposite synthesized under various preparation conditions fell in the range of 20 -50 nm. The effects of the pH, reactant composition, and solvent content in the reaction mixture on the thermal and mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…The rubbery modulus increases, mainly from 10 wt% of silica content. This strong increase of the rubbery plateau modulus agrees well with the literature [91,111,117,131,148] and seems to be related with the percolation of the silica phase, forming a continuous network extended throughout the sample for silica contents higher than that threshold, which constrains the long distance cooperative motions of the copolymer chains. The fact that only for these silica contents a continuous densified silica structure was obtained after performing a pyrolysis and removal of the organic phase, is consistent with this observation.…”
Section: Characterization Of P(ema-co-hea)/sio 2 Nanocompositessupporting
confidence: 90%
See 3 more Smart Citations
“…The rubbery modulus increases, mainly from 10 wt% of silica content. This strong increase of the rubbery plateau modulus agrees well with the literature [91,111,117,131,148] and seems to be related with the percolation of the silica phase, forming a continuous network extended throughout the sample for silica contents higher than that threshold, which constrains the long distance cooperative motions of the copolymer chains. The fact that only for these silica contents a continuous densified silica structure was obtained after performing a pyrolysis and removal of the organic phase, is consistent with this observation.…”
Section: Characterization Of P(ema-co-hea)/sio 2 Nanocompositessupporting
confidence: 90%
“…This loss of thermal stability of the silica hybrids was also observed by Costa et al [109] in PHEMA/SiO 2 composites, who explained it on the basis of a decrease in hydrogen-bonding among copolymer chains promoted by the presence of silica. Other authors [89,111] observed the opposite effect and attributed it to a good homogeneity due to nanoscale mixing and to relatively strong heterogeneous hydrogen bonds tethering silica and polymer chains. On the one hand, the fact that the decomposition profile only seems to be affected by silica contents below 15 wt%, and on the other hand that it is the first weight loss stage which increases in importance, suggest that high temperatures during the measurements allow condensations between non-condensed silanol groups to start again.…”
Section: Characterization Of P(ema-co-hea)/sio 2 Nanocompositesmentioning
confidence: 96%
See 2 more Smart Citations
“…In the last years, the polymer doped with metal oxide nanoparticles have been studied as alternative materials for optical applications, including planar waveguide devices and microoptical elements [10][11]. The polymers modified by metal oxide nanoparticles have been prepared by sol-gel process, by polymerization of monomer containing nanoparticles and by dispersing of nanoparticles in a polymeric matrix [12][13]. The presence of nanoparticles in polymer improves the mechanical, electrical and optical properties of the material and it is possible to control these properties, including the refractive index, by concentration [14].…”
Section: Introductionmentioning
confidence: 99%